Covid-19 School Closures in Low- and Middle-income Countries: Emergent Perspectives on the Role of Educational Technology - Katy Jordan (Commonwealth of Learning, 2020)
The Covid-19 pandemic ushered in school closures at an unprecedented scale and prompted educational systems to find alternative teaching models at short notice. The role for educational technology in low- and middle-income countries (LMICs) has recently become the focus of much discussion. While prompted by the pandemic, the discussions surface latent issues in educational systems, and the perspectives and ambitions of organisations in relation to educational technology and LMICs. The influence of the discussions during this period is likely to extend beyond the initial crisis, and warrants investigation. This paper presents a thematic analysis, using a grounded theory approach, of documents published online between February and April 2020. Five themes emerge, in relation to access, responses, support from carers, teachers and communities, educational quality and the future.